Critical urbanisation transitions in Malaysia: the challenge of rising Bernam to Linggi basin extended mega urban region - Abdul Samad Hadi; Shaharudin Idrus; Abdul Hadi Harman Shah; Ahmad Fariz Mohamed (Universiti Kebangsaan Malaysia, 2011)
A three phase urbanisation transition is proposed to capture the urbanisation path shown by urban behaviour in the country; namely the phases of nascent, pseudo and the rise of the extended mega urban region. It is recognised that modern urban centres in the country were founded by the British administration of the country as from the 18th century, albeit the existence of the Melaka empire in earlier centuries. These urban centres were mainly administrative centres to administer law and order in order to sustain the exploitation of tin and rubber production, in addition to the provision of goods and services. Urban life in these centres were generally ‘foreign’ to the conception of life of the local people who participated marginally in the market economy controlled by British capital. The second urbanisation transition is the shift from the nascent urbanisation phase moving into the phase of what we have been widely referring to as the pseudo-urbanisation phase, taking place roughly after the end of World War II, when the country witnessed the movements of rural youths, dominantly males at first, to seek jobs in the limited and fragmented urban labour markets. Urban poverty was rampant. The third critical transition to the urbanisation experience of Malaysia lies in the outcome of the New Economic Policy (NEP), 1970 and the subsequent development policies after the NEP. The development policies, strategies, programs and activities produced widespread social, economic, environmental and spatial changes, seen in the growing extended mega urban region, stretching from the Bernam river basin on the Perak-Selangor border to the Linggi river basin bordering Negeri Sembilan and Melaka